CONFIDENTIALITY OBLIGATION OBSTACLES IN THE PROCESS OF SOCIAL WORK - Dirgėlienė, Indrė (Acta Paedagogica Vilnensia, 2010)
The goal of the article was to reveal confidentiality obligation obstacles in the process of social work based on interaction. The article is based on the report of the research project “Designing of a Model of Applying Supervision for the Enhancement of Social Workers’ Professional Competences”. The project was funded by the Lithuanian State Science and Studies Foundation. Researchers: N. Večkienė, J. Ruškus, I. Dirgėlienė, A. Kiaunytė, V. Kanišauskaitė, 2007.The research was conducted in institutions providing social services in June–August, 2007. Respondents from 81 institutions were selected to fill questionnaires.Characteristics of a social worker as an obstacle to maintaining confidentiality are identified by social workers dealing with problems of poverty, addiction and disability. As well as “complicated” risk groups where empowerment does not always provide a possibility to see a rapid and striking result. These are problems resulting into a threat of “burn out syndrome” in case a social worker does not look for ways of relaxation and reflection inducement. Confidentiality obligation obstacles identified by employees of the biggest Lithuanian towns and sub-divisions are different.A substantially higher percentage of employees of sub-divisions identify characteristics of a social worker as an obstacle to confidentiality maintaining. It might be explained by lack of information about support, new methods and technologies. The level of education is different as well. Demographic data of the respondents demonstrate that education of social workers working in towns and regional centres is higher (analysis of demographic data).Research data revealed that the respondents relating confidentiality obligation obstacles to characteristics of a social worker link theoretical knowledge and practice less. Theory and practice relation, i.e. competence to apply theoretical knowledge in practice assures better self-regulation skills. Ability to relate theory and practice is characteristic of the respondents with university education (masters and bachelors), they have better self-regulation skills. They have formed reflection skills and are ready to accept a supervision service they get familiar with in the process of studies and during their practice. Supervision as the possibility to develop professional competences of a social worker is important to those respondents that are already ready to accept it and supervision should help them to form and develop reflection skills as a preventive measure of a “burn out syndrome”.
Keywords: social work; confidentiality; interaction; reflection; supervision